Geomorphic design and modelling at catchment scale for best mine rehabilitation – The Drayton mine example (New South Wales, Australia). (April 2019) - Hancock, G.R.; Duque, JF Martín; Willgoose, G.R.
Abstract: Computer modelling and design tools can assist in environmental management. In particular, post-mining landscapes with large volumes of materials require shaping for optimal erosional stability and ecological and visual integration into the surrounding undisturbed landscape. This paper evaluates the complementary capabilities of landscape evolution modelling (SIBERIA) and geomorphic design software (Natural Regrade with GeoFluv). An existing 11.5-ha waste rock dump (Hunter Valley, New South Wales, Australia) served as the study site. The SIBERIA modelling demonstrated that geomorphic design reduced erosion by half that of conventional designs while being able to store an extra 7% of mine waste volume. Additionally, the spatial pattern of gullying was able to be predicted by modelling, which allowed management in subsequent geomorphic design, and successively more stable patterns. In conclusion, the joint use of the Natural Regrade with GeoFluv geomorphic design software with the SIBERIA landscape evolution model showed complementary capabilities for enhancing mine rehabilitation. Highlights: Computer models and modelling design greatly improve mine site rehabilitation. We demonstrate the SIBERIA and Natural Regrade with GeoFluv software. The complementary tools reduce erosion yet can increase landscape volume.